Territorialização da saúde : determinantes ambientais e o cotidiano das equipes de saúde da família – Lagarto (SE) - Machado, Rosangela Fátima de Oliveira (2019)
Primary Health Care has as one of its pillars the link between professionals and the population. Territorialization of health is one of the tools to identify social and environmental aspects that can contribute to reflection and actions more appropriate to each place, according to their specific demands. The Federal Constitution proclaims the promotion of health and the prevention of injuries as fundamental components in the daily work of the team. Although the bacterial revolution weakened this thesis for a while, socio-environmental determinants continued to be studied and in the last few years it became world-wide, based on the considerations and referrals of the World Health Organization (WHO) to its affiliated countries. However, the biomedical model, centered in the body, still predominates. The proposals related to the identification of the territory and its determinants as components of the health-disease process have not been considered with the emphasis that is necessary. The result of this translates into high index of diseases typically of environmental origin. The objective of this work is to investigate how environmental determinants are observed, perceived, portrayed, related and worked by the health team in the municipality of Lagarto (SE), within the territory established as the area of activity. The methodological procedures are based on qualitative research, which provides a deeper understanding of the perception and action of health professionals. Documentary research, interviews and field study with the health teams favor the construction of the study. The results confirm the importance of including environmental determinants in health actions and show the possibility of constructing a model that contributes to the inclusion of them in the routine of the family health team professionals' agenda. Lagarto (SE) is an example of the iniquities and problems associated with water supply and sanitation due to its porosity and soil permeability characteristics, granular aquifer type that contaminate the water table. Therefore, the territory must be the priority in the work of the professionals and the place of listening. In addition, the territory as the basis of health promotion reveals the valuation of health to the detriment of the disease.